(untitled) (Journal of Engineering, 2004)
One of the major advantages of digital photogrammetry is the potential to automate production processes efficiently , thus substantially improving the price performance ratio for photograrnmetric products. The other major advantage of digital photogrammetry is increasing the accuracy of the final output results .Image processing and computer vision techniques have suc,pessfully been employed for facilitating automated procedures in digital aerial images such as interior orientation , relative orientation , point transfer in photogrammetric block triangulation , and the generation of DTM S .Digitat a.erotriangulation including image import and image minification , interior orientation , point transfer , control point measurements , bundle block adjustment , ’*’hich is one of the most complex processs in <tigital photogrammetry and the automation of this process was one of the challenges in the photrrgra.mmetric commturity in the early nineties .The goal of thjs research is building a digital aerotriangulation package that have been implemented on Baghdad University a.s study area using Pentiurn [U personal computer with Jaderia prograln that have been written by the researcher herself , to be the first trial of digital aerotriangulation in Baghdad University .The resurlts of the implemented work vras RMSx: 8.1 l4m , RMSy = 8.372m & RMSz :22.785m , and this is iue to a lot of errors that have been faced during the various phases of this work..